2008
DOI: 10.1128/jcm.01626-07
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Aspects of Invasive Streptococcus pyogenes Infections in Denmark during 2003 and 2004

Abstract: Active surveillance of invasive group A streptococcal (GAS) infections was conducted in Denmark during2003 and 2004 as a part of the Strep-EURO initiative. The main objective was to improve understanding of the epidemiology of invasive GAS disease in Denmark. During the 2 years, 278 cases were reported, corresponding to a mean annual incidence of 2.6 cases per 100,000 inhabitants. The vast majority of isolates, 253 (91%), were from blood, with the remaining 25 (9%) being from cerebrospinal fluid, joints, or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
112
3
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(138 citation statements)
references
References 59 publications
16
112
3
5
Order By: Relevance
“…46,47 Studies suggest the M type distributions of many resistance traits are not well conserved over time and space. 22,34,36,[46][47][48] However, a recent US study showed that even these highly variable traits segregate significantly with M type over shorter periods of time. 44 Macrolide resistance offers an excellent example of a phenotype that is more highly correlated with M type and for which M typing offers a significant degree of predictive power.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 3 more Smart Citations
“…46,47 Studies suggest the M type distributions of many resistance traits are not well conserved over time and space. 22,34,36,[46][47][48] However, a recent US study showed that even these highly variable traits segregate significantly with M type over shorter periods of time. 44 Macrolide resistance offers an excellent example of a phenotype that is more highly correlated with M type and for which M typing offers a significant degree of predictive power.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Moreover, the types that are most dominant in invasive categories, and hence those responsible for the observed decrease in diversity, are almost always the same-most notably M1 and M3. 8,12,18,[32][33][34][35][36] Similar dynamics, including decreased diversity and the dominance of specific types, are apparent in studies of more specific clinical phenomena such as fatality, associated with M1, M3 and M12, 32 puerperal sepsis, associated with M28, 34,36,37 STSS, associated with M1 and M3, 12,35,38 epidemic ARF, associated with M5 and M18, 39 and geographically widespread epidemic behavior, most commonly associated with M1. 2,12 Despite genetic changes in these serotypes over time, including alterations of virulence and antibiotic resistance factors, these associations generally remain stable.…”
Section: Clinical Relevance Of M Typementioning
confidence: 99%
See 2 more Smart Citations
“…The recommended medical treatment for severe GAS disease includes a combination of a 毬 -lactam and clindamycin since no resistance has yet been reported against these drugs [13] , although local conditions and tissue ischemia, prevent adequate delivery of antibiotics in the area, and prevent bacterial destruction via aerobic mechanisms [9] , thus surgical debridement is imperative [14] . Both of our patients received early in their course an appropriate combination of antibiotics which nevertheless, did not delay or confine the extent of the infection.…”
Section: Discussionmentioning
confidence: 99%